VALIDATING A WORK ATTRIBUTE QUESTIONNAIRE FOR PHARMACEUTICAL SALES REPRESENTATIVES AMIDST COVID-19 IN NIGERIA: A STUDY USING CONFIRMATORY FACTOR ANALYSIS - Emma , L. W. (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
The COVID-19 pandemic has had significant adverse effects on the work-life characteristics of sales professionals in the pharmaceutical industry. Work attributes are crucial factors that can determine a person’s effectiveness in a particular job role. Therefore, this study aimed to validate a 13-item questionnaire on the work attributes of pharmaceutical sales executives involved in pharmaceutical marketing in Nigeria during the COVID-19 lockdown period. A confirmatory factor analysis (CFA) was used to develop a structural model from the initial 13-item factor structure obtained from a previous exploratory factor analysis (EFA) study. The results show that community education was the most important work attribute, while limited access to customers was the least important. The CFA confirmed the structural model produced by the EFA study. Additionally, it confirmed the model’s validity and its construct reliability, although divergent validity can be improved with more constructs. The study’s findings are crucial for the pharmaceutical industry to understand the work attributes required during a pandemic and adapt their roles and work structures accordingly